Структурні компоненти інтелектуального капіталу в умовах активізації технологічних інновацій та соціокультурних зрушень - Пальчевич, Г. Т.; Козинець, Г. О.; Palchevich, G.; Kozynets, G. (ХНУ, 2019)
У статті досліджено формування структури інтелектуального капіталу в умовах інноваційного розвитку економіки. Визначено фундаментальну роль людського капіталу серед структуроутворюючих елементів інтелектуального капіталу суспільства. Висвітлено значення та функції інституційно-інфраструктурної складової інтелектуального капіталу. Охарактеризовано умови формування інформаційного та клієнтського капіталів як важливих компонентів інтелектуального капіталу. Доведено тісну взаємозалежність окремих структурних елементів інтелектуального капіталу та синергетичний ефект від їх взаємодії. Intellectual capital is truly considered the main social wealth, the movement of development innovational economy able to compete. The aim of article is the survey of structural components of intellectual capital in the condition of technologic ally oriented innovation development and social and cultural social transformations. Human, informational, contractoral and institutional and infrastructural capitals are organically interacted in the complex of national intellectual capital. Human capital in the complex of intellectual capital plays the fundamental role as the formation and effective using of other structural components of intellectual capital and it directly depends upon the level of its development. Superstructure of manysided and endless inner interaction of all compound part soft intellectual capital, maintenance of its mutual relations with outer stakeholders is held with the help of institutional and infrastructural capital. The results of intellectual, innovational and scientific technical activity, patents, no - how, program products, the data base, the results of NDDKR, informational and telecommunical technologies, technological, scientific and technical, social and economical and spiritual in formation, informational system and informational recources belong to informational capital. Contractoral capital is the system of reliable and longtermed, confidential and mutual profitable form al and nonformal relations between the state and outer economical contractors and subjects of inner national environment of intellectual capital development (humans, subjects of economy, managing institutes ets.) which were completed in the process of formation and using the intellectual capital and they promote the stability of development of national economy, innovational and scientific and technical spheres, the increasing of national income and level of ability of the state to compete, and also the increasing of reserve recourses of improvement of intellectual part of economical development in perspective.
Structural components of intellectual capital in the condition of technological innovations and social and cultural movements
Keywords: інтелектуальний капітал; технологічні інновації; людський капітал; інформаційний капітал; контрагентський капітал; інституційно-інфраструктурний капітал; трансфер технологій; цифрова економіка; intellectual capital; technological innovations; human capital; informational capital; institution and infrastructural capital; transfer of technologies; numeral economy